Evaluation of Infiltration in Furrow Irrigation Part 1: Recession Flow - Lee, Teang Shui; Walker, W. R. (1992)
Recession flow in a large field can be significant from the point of view of water-use efficiency. This is particularly important in the case where the furrow field is long, thus the receding flow can contribute to the irrigation of crops. Indeed, recession flow is very significant in the surge method of furrow irrigation. In the continuous mode of operation in very long furrows the amount of recession flow can be significant. Herein is presented the mathematical modelling of the recession flow. The analytical procedure is based on the kinematic wave approach used for the simulation of the advance-flow trajectory for furrows. This resulting recession simulation was found to be very useful for the evaluation of the basic infiltration rate in a furrow.